2020
DOI: 10.5093/jwop2019a27
|View full text |Cite
|
Sign up to set email alerts
|

An Affective Events Model of the Influence of the Physical Work Environment on Interpersonal Citizenship Behavior

Abstract: A B S T R A C TBased on the Affective Events Theory (AET), this paper proposes a model of how the level of organizational citizenship behavior (OCB) directed at individuals (peers) (OCB-I) declines to the extent that physical conditions in offices make employees experience crowding perceptions and privacy invasions from peers. We hypothesize that: 1) crowding perceptions and privacy invasions by peers are related to employees' feelings of relational conflict with peers; 2) relational conflict negatively relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
(100 reference statements)
2
5
0
Order By: Relevance
“…In fact, in line with Carter et al [ 88 ], caregivers’ perceived spatial-physical comfort in the work environment increases the likelihood of performing OCBs. In particular, the relationships emerged between perceived comfort and altruistic behaviors, this is in line with the negative effects of low comfort on workers’ altruism found in the study by Zoghbi-Manrique-de-Lara et al [ 87 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, in line with Carter et al [ 88 ], caregivers’ perceived spatial-physical comfort in the work environment increases the likelihood of performing OCBs. In particular, the relationships emerged between perceived comfort and altruistic behaviors, this is in line with the negative effects of low comfort on workers’ altruism found in the study by Zoghbi-Manrique-de-Lara et al [ 87 ].…”
Section: Discussionsupporting
confidence: 86%
“…Even though it has been shown that office physical features such as noise, lighting conditions, temperature, and indoor air quality impact the attitudes, behaviors, productivity, and satisfaction of employees [ 68 ], and that the low quality of workplace design can elicit lower work satisfaction, lower job productivity, poorer health, and higher mental fatigue [ 69 ], less attention has been placed on perceived design quality in relation to workers’ behaviors and well-being. Among those addressing these concerns, Zoghbi-Manrique-de-Lara et al [ 87 ], evidenced the negative influence of crowded physical workspaces with low privacy on organizational citizenship behaviors in favor of others (OCB-I) in a study with workers in open-space facilities. Carter and colleagues [ 88 ] found that satisfaction with physical workspace and perceived quality of the physical workplace are drivers of OCBs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Choi et al( 2011 ) found that when employees face innovative activities at work, they will feel cheer or delight because of the benefits brought by innovation, and also feel anxious or helpless when facing new things. For setting up open-plan offices, an internal workplace event, employees also experience positive or negative social-related affective reactions, such as positive affective concerns for colleagues or negative affective reactions like tensions of privacy violation ( Ashkanasy et al, 2014 ; Zoghbi-Manrique-de-Lara and Sharifiatashgah, 2020 ). Therefore, these work events can trigger both positive and negative affective reactions.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The Affective Events Theory (AET) [ 12 ] explains the relationship between the internal influences of employees, represented in affective events, or moods and emotions, and their reactions to events that happen in the workplace and impact their performance, feelings, attitudes, and job satisfaction levels. The theory differentiates between affective or influential work behaviors and cognitive–based behaviors that act as job satisfaction predictors [ 28 ]. Individuals within organizations behave according to their spontaneous feelings that change from one moment to another in the workplace.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%